Absence of Helicobacter pylori is not protective against peptic ulcer bleeding in elderly on offending agents: lessons from an exceptionally low prevalence population - Yeong, Yeh Lee; Nordin, Noridah; Syed Abdul Aziz, Syed Hassan; Menon, Jayaram (PeerJ, 2014)
Aim. Helicobacter pylori (H. pylori) infection is exceptionally rare in population from the north-eastern region of Peninsular Malaysia. This provides us an opportunity to contemplate the future without H. pylori in acute non-variceal upper gas- trointestinal (GI) bleeding. Methods. All cases in the GI registry with GI bleeding between 2003 and 2006 were reviewed. Cases with confirmed non-variceal aetiology were analysed. Rockall score >5 was considered high risk for bleeding and primary outcomes studied were in- hospital mortality, recurrent bleeding and need for surgery. Results. The incidence of non-variceal upper GI bleeding was 2.2/100,000 person- years. Peptic ulcer bleeding was the most common aetiology (1.8/100,000 person- years). In-hospital mortality (3.6%), recurrent bleeding (9.6%) and need for surgery (4.0%) were uncommon in this population with a largely low risk score (85.2% with score 5). Elderly were at greater risk for bleeding (mean 68.5 years, P D 0.01) espe- cially in the presence of duodenal ulcers (P D 0.04) despite gastric ulcers being more common. NSAIDs, aspirin and co-morbidities were the main risk factors. Conclusions. The absence of H. pylori infection may not reduce the risk of peptic ulcer bleeding in the presence of risk factors especially offending drugs in the elderly.